2017
DOI: 10.1162/jocn_a_01069
|View full text |Cite
|
Sign up to set email alerts
|

Neural Systems Underlying Individual Differences in Intertemporal Decision-making

Abstract: Excessively choosing immediate over larger future rewards, or delay discounting (DD), associates with multiple clinical conditions. Individual differences in DD likely depend on variations in the activation of and functional interactions between networks, representing possible endophenotypes for associated disorders, including alcohol use disorders (AUDs). Numerous fMRI studies have probed the neural bases of DD, but investigations of large-scale networks remains scant. We addressed this gap by testing whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…While in the MRI scanner, participants performed a delay discounting task optimized for fMRI studies. The details of this task, in which participants selected between sets of smaller, immediate hypothetical monetary rewards (“ Now ”), or larger, delayed rewards (“ Later ”), have been reported previously (Boettiger et al, 2007 , 2009 ; Altamirano et al, 2011 ; Smith and Boettiger, 2012 ; Kelm and Boettiger, 2013 ; Smith et al, 2014a , 2015 ; Elton et al, 2017 ) and are further detailed in the Supplementary Materials. Subjects underwent six consecutive functional MRI scans (~8 min per scan) each of which included 32 Now -vs.- Later decisions, consisting of four decision trial types presented psuedorandomly: “WANT,” “DON'T WANT,” “SOONER,” or “LARGER.”…”
Section: Methodsmentioning
confidence: 99%
“…While in the MRI scanner, participants performed a delay discounting task optimized for fMRI studies. The details of this task, in which participants selected between sets of smaller, immediate hypothetical monetary rewards (“ Now ”), or larger, delayed rewards (“ Later ”), have been reported previously (Boettiger et al, 2007 , 2009 ; Altamirano et al, 2011 ; Smith and Boettiger, 2012 ; Kelm and Boettiger, 2013 ; Smith et al, 2014a , 2015 ; Elton et al, 2017 ) and are further detailed in the Supplementary Materials. Subjects underwent six consecutive functional MRI scans (~8 min per scan) each of which included 32 Now -vs.- Later decisions, consisting of four decision trial types presented psuedorandomly: “WANT,” “DON'T WANT,” “SOONER,” or “LARGER.”…”
Section: Methodsmentioning
confidence: 99%
“…ICA has been proposed to have several advantages over GLM, including less susceptibility to functional heterogeneity and the ability to separate inhibitory and excitatory influences on neuronal activity (Xu et al, 2015; Xu et al, 2016). ICA is a data-driven, network-based computational procedure that has been used to identify functional alterations in the multiple brain networks that contribute to cognitive control (Worhunsky et al, 2013), decision-making (Elton et al, 2017), and during resting-state (Ding and Lee, 2013) in individuals with substance-use disorders. Thus, the current study aimed to extend previous investigations of loss-chasing behavior by examining activity in functional brain networks in individuals with gambling disorder (GD), individuals with cocaine-use disorder (CUD) and a healthy comparison (HC) sample.…”
Section: Introductionmentioning
confidence: 99%
“…Casey et al (2011) reported that children who delayed their gratification (high delayers) showed stronger activation in the inferior frontal gyrus during a response inhibition task in adulthood than did those who did not delay their gratification (low delayers). Moreover, adult brain imaging studies repeatedly show that high delayers show stronger lateral prefrontal activations than low delayers do (Ballard & Knutson, 2009;Elton, Smith, Parrish, & Boettiger, 2017). However, it is still unknown whether behavioral performance is related to activations in the prefrontal regions in young children.…”
mentioning
confidence: 99%